Factors affecting purchase intention toward online shopping / Azlan Sairin - Sairin, Azlan (2014)
Nowadays, the online shopping is popular among the consumer to make them ease purchase through the internet. Interestingly, the economic report was found consumers majority has abandon their shopping cart. This research is a study in the area of consumer online purchase intention. The purpose of the study is to examining the correlations of the antecedents that affect the consumers purchase intention toward online shopping. The research design use in the study is quantitative correlation design for gathering the necessary data. The data was obtained through random sampling given to the respondents at the Kota Kinabalu area. Form the findings, the gender as demographic profile examined as affected factors in the online purchase intention. Perceived site quality was indentified to be positively related to the consumer online purchase intention. Likewise the trust also confirmed have positive related to the consumer online purchase intention.